CURRENT AFFAIRS IN PASSENGERS RIGHTS PROTECTION IN THE EUROPEAN UNION (EU and comparative law issues and challenges series (ECLIC), 2018)
Developed passenger transport includes new issues related to liability issues as well as issues of passenger rights protection. The protection of passengers rights is carried out in accordance with the provisions of international treaties, European and national legislation. Carriers are liable for passengers (in case of death, injury) and their luggage (loss, damage) and in some cases for delay so passengers may be entitled to compensation. The protection of passengers rights is imperative in the creation of transport law regulations as set out by the Commission in the 2001 White Paper – ‘European transport policy for 2010: time to decide’. The European Union has recognized the need for wider protection of passengers rights and has adopted a series of regulations and directives aimed at protecting the interests of passengers and strengthening their rights in all modes of transport (road, rail, air, maritime and inland waterways). Application of EU passenger rights legislation should be uniformed. In order to increase the number and frequency of passenger transport, appropriate regulations are needed. European rules pay special attention to better organization, accessibility and transportation for disabled persons and persons with reduced mobility. The rights of passengers in multimodal transport should be also appropriately regulated. Despite the great efforts and the existence of these rules, there are still some open questions, legal gaps, problems in implementation and application of rules as well as problems regarding exercising passenger rights. In this paper, we will look at existing problems, obstacles to more efficient application of the Regulations and make recommendations for further action and amending legislation in order to increase the protection of the passengers rights.